A GERIATRIC COMMUNICATION SKILLS TRAINING FOR ONCOLOGY CLINICIANS: EVALUATION OF PROGRAM LEARNING. (16th November 2018) - Banerjee, S; Manna, R; Alexander, K; Gangai, N; Alici, Y; Nelson, C; Parker, P; Korc-Grodzicki, B
Abstract: Oncology clinicians who treat older adults with cancer face numerous communication challenges such as finding the right words to communicate with patients with sensory, functional, or cognitive difficulties, checking their medical understanding, and asking about specific symptoms/impairments. Given that the over-65 population is the fastest growing segment of the US population and nearly 60% of all cancers occur in patients over-65 years, the number of older adults with cancer is predicted to dramatically increase with this aging trend. Consequently, all oncology clinicians will face the challenges of caring for this aging population. Therefore, to improve quality of communication in geriatric oncology care, a multidisciplinary team at Memorial Sloan Kettering developed a day-long novel intervention, Geriatric Comskil Training for oncology clinicians. The Geriatric Comskil Training is comprised of three 2-hour modules: Geriatrics 101, Cognitive Syndromes, and Shared Decision Making. A single arm pre-post intervention design was utilized to examine learning, i.e., changes in participant self-efficacy (self-reported measure) and uptake of communication skills (using Standardized Patient Assessments or SPAs, 12-minute video recorded interactions between the clinician and the standardized patient). Participants (N=97) reported significant improvements in overall self-efficacy to communicate with older adults, t(64), =-10.67, p<.001 from pre- (M=3.48, SD=.74) to post-training (M=4.35, SD=.44). Evaluation of coded SPAs demonstrated significant uptake of agenda setting skills: pre-training M=.26, SD=.54, post-training M=.91, SD=1.05;t(45)=-3.64, p<.001; and information organization skills: pre-training M=.50, SD=.78, post-training M=.89, SD=.97;t(45)=-2.66, p<.01. The Geriatric Comskil Training demonstrated improvements in clinician self-efficacy, and observed uptake of communication skills. Examination of clinician communication in clinics and impact on patient outcomes is further warranted.